Primitivism and Feminism in Contemporary Art - Ocampo, Estela (Arte, Individuo y Sociedad, 2016)
For the colonialist mentality of the 19th century, black people have an extraordinary sexuality and lust. In the metropolis, the equivalent was the sexed woman, the prostitute. In the early years of the 20th century, this tandem, prostitute-colonized, is used by the avant-garde artists as an element of confrontation with the dominant morality. Women artists, with a feminist aim, are the main ones who use primitivism associated to women in their criticism to stereotypes. One of the pioneer figures is Hannah Höch, specially in her series From an Ethnographic Museum, in which she associates feminine figures and primitive art objects. In the seventies, some performer artists like Carolee Schneemann or Ana Mendieta vindicate the feminine body as a meaning of Origin and Fertility, the same significance that it has in primitive cultures. The sculpture Maman, by Louise Bourgeois, can be framed within the same context. The element of social criticism, still present nowadays, can be seen in the works by Guerrilla Girls.